2020
DOI: 10.1097/jcp.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Adherence of Monitoring Antipsychotic Use for Nonpsychotic Indications in Children and Adolescents

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…A study by McLaren et al has shown that most child psychiatrists reported being aware of the CPGs for antipsychotic drug monitoring,27 while a study by Mangurian et al has shown that a large proportion of the primary care providers seem to be unaware of the consensus guidelines 30. Nevertheless, previous studies have demonstrated that monitoring rates were low and remained low after implementation of monitoring guidelines 12 14. As far as we know, no studies have been conducted that evaluated whether (a) more clear and applicable CPGs lead to better CPG adherence, and (b) whether good adherence to such clinical guidelines for the monitoring of ADR-related parameters indeed leads to better clinical outcomes such as less ADRs or better recognition and management thereof.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by McLaren et al has shown that most child psychiatrists reported being aware of the CPGs for antipsychotic drug monitoring,27 while a study by Mangurian et al has shown that a large proportion of the primary care providers seem to be unaware of the consensus guidelines 30. Nevertheless, previous studies have demonstrated that monitoring rates were low and remained low after implementation of monitoring guidelines 12 14. As far as we know, no studies have been conducted that evaluated whether (a) more clear and applicable CPGs lead to better CPG adherence, and (b) whether good adherence to such clinical guidelines for the monitoring of ADR-related parameters indeed leads to better clinical outcomes such as less ADRs or better recognition and management thereof.…”
Section: Discussionmentioning
confidence: 99%
“…A monitoring instruction was defined as an instruction on measuring a physical, laboratory or observational ADR-related parameter before or during antipsychotic drug treatment. In total, 13 ADR-related parameters were included, based on the cardiometabolic, endocrine and extrapyramidal ADRs that can be caused by antipsychotic drugs 13 14. The physical parameters included were weight, height, BMI, waist circumference, blood pressure, pulse and ECG.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 , 34 The prescription patterns could be changed over time according to the patient’s symptoms and disease severities. 35 , 36 , 37 , 38 , 39 Thus, we might more precisely estimate the risk of movement disorders and seizures associated with the use of antipsychotics and antidepressants in the treatment of children and adolescents with depression.…”
Section: Discussionmentioning
confidence: 99%